Data warehouse - opportunity for local authorities - Šimonová, Stanislava (Univerzita Pardubice, 2004)
Local government exists in a very complex organizational environment, which has been subjected to an ever increasing pace of changes. This situation has generated a huge impact on the local government's reaction towards two major elements in is administration - decision making and technology approaching. The data warehouse technology offers a solution to this problem. But there are various obstacles that inhibit the government from adopting this technology.
Keywords: místní správa; datové sklady; rozhodovací procesy; Informační technologie